PELAKSANAAN ADAT BARALLEK SEBELUM AKAD NIKAH TINJAUAN HUKUM ISLAM (Studi Kebiasaan Masyarakat Rantau Gedang Kabupaten Aceh Singkil) - Azharuddin Azharuddin (IAIN Padangsidimpuan, 2022)
Walimatul 'ursy which the people of Rantau Gedang call the barallek custom is always carried out when a marriage event occurs, which is unique in that the local community often carries out the barallek custom before the wedding. The purpose of this study is to analyze why the implementation of the barallek custom before the marriage contract is often carried out by the people of Rantau Gedang. This research is an empirical juridical research, because this research looks at the rule of law with practices that occur in the field, while the legal approach used is a legal anthropological approach because this problem is analyzed based on 'urf in Islamic law. The results showed that the traditional practice of barallek in the Rantau Gedang community occurred after carrying out the marriage contract and before carrying out the marriage contract, this first practice usually has a gap between the marriage contract and the barallek custom which sometimes takes weeks and months. The second practice is carried out by the barallek custom first, then after the culmination of the barallek tradition is completed, the marriage contract is carried out. According to Islamic law, the practice of barallek custom before the marriage contract is carried out is in accordance with 'urf sahih, because the purpose of carrying out the barallek custom before the marriage contract is so that the bride's marriage can be witnessed by all families and the general public, apart from that it is also to strengthen the relationship between the two large families. the bride and groom.